A Sri Lankan child with hypersplenism secondary to pre-hepatic portal hypertension, successfully managed with partial splenic artery embolization: a case report and review of the literature - Visvalingam Arunath; Manoj Sanjeewa Liyanarachchi; Sundarraajah Gajealan; Kumudu Weerasekara (SpringerOpen, 2022)
Abstract Background Hypersplenism, one of the major complications of portal hypertension, is traditionally treated by splenectomy. However, partial splenic artery embolization is an evolving minimally invasive intervention to treat these patients effectively. Case presentation A 13-year-old girl was referred for further evaluation of isolated splenomegaly with pancytopenia. She did not have bleeding manifestations or features of anemia. She never had hematemesis or melena. On examination, she was pale. Abdominal examination revealed massive splenomegaly of 10 cm below the costal margin without hepatomegaly. Rest of the examination was unremarkable. Her investigations revealed a white cell count of 1700/mm3 (neutrophils 9.8% and lymphocytes 88.7%), hemoglobin 9.5 g/dL and platelet count 42,000/mm3. Blood picture showed pancytopenia without abnormal cells. Her reticulocyte count was 1.9%. Complete liver profile was normal. Abdominal ultrasonography revealed massive splenomegaly with the oblique length of 17 cm and normal echogenic liver with normal size. Cavernous transformation of portal vein with portal hypertension was evident. Mesenteric angiogram showed portal vein thrombosis and markedly tortuous splenic artery. Anti-nuclear antibodies and double-stranded DNA were negative. Ham test and urine for hemosiderin were negative. Clauss fibrinogen assay was normal. Hemoglobin high performance liquid chromatography for hemoglobin subtypes was normal. Anti-phospholipid antibodies were negative. JAK2 V617F mutation was not identified. Diagnosis of pre hepatic portal hypertension was made. Her upper gastrointestinal endoscopy was normal. Partial splenic artery coil embolization was done by interventional radiology team. Vaccines against capsulated organisms were given. Post-procedure contrast abdominal computed tomography revealed infarction of approximately 70% of the spleen and blood counts were improved. Index case is in the follow up for 3 years. She is on penicillin prophylaxis with regular blood count and annual upper gastrointestinal endoscopy monitoring. Conclusions Minimally invasive interventions such as partial splenic artery embolization should be considered in managing the patients with hypersplenism secondary to portal hypertension.